Comprehensive Biological Potential, Phytochemical Profiling Using GC-MS and LC-ESI-MS, and In-Silico Assessment of Strobilanthes glutinosus Nees: An Important Medicinal Plant - Marya Aziz; Saeed Ahmad; Umair Khurshid; Irfan Pervaiz; Arslan Hussain Lodhi; Nasrullah Jan; Sameera Khurshid; Muhammad Adeel Arshad; Mohamed M. Ibrahim; Gaber A. M. Mersal; Fahaad S. Alenazi; Ahmed Awadh Saleh Alamri; et al. (Molecules, 2022)
Plants of the genus Strobilanthes have notable use in folklore medicines as well as being used for pharmacological purposes. The present work explored the biological predispositions of Strobilanthes glutinosus and attempted to accomplish a comprehensive chemical profile through GC-MS of different fractions concerning polarity (chloroform and n-butanol) and LC-ESI-MS of methanolic extract by both positive and negative ionization modes. The biological characteristics such as antioxidant potential were assessed by applying six different methods. The potential for clinically relevant enzyme (α-amylase, α-glucosidase, and tyrosinase) inhibition was examined. The DPPH, ABTS, CUPRAC, and FRAP results revealed that the methanol fraction presented efficient results. The phosphomolybdenum assay revealed that the n-hexane fraction showed the most efficient results, while maximum metal chelation potential was observed for the chloroform fraction. The GC-MS profiling of n-butanol and chloroform fractions revealed the existence of several (110) important compounds presenting different classes (fatty acids, phenols, alkanes, monoterpenes, diterpenes, sesquiterpenoids, and sterols), while LC-ESI-MS tentatively identified the presence of 44 clinically important secondary metabolites. The n-hexane fraction exhibited the highest potential against α-amylase (497.98 mm ACAE/g extract) and α-glucosidase (605.85 mm ACAE/g extract). Significant inhibitory activity against tyrosinase enzyme was displayed by fraction. Six of the prevailing compounds from the GC-MS study (lupeol, beta-amyrin, stigmasterol, gamma sitosterol, 9,12-octadecadienoic acid, and n-hexadecanoic acid) were modelled against α-glucosidase and α-amylase enzymes along with a comparison of binding affinity to standard acarbose, while three compounds identified through LC-ESI-MS were docked to the mushroom tyrosinase enzyme and presented with significant biding affinities. Thus, it is assumed that S. glutinosus demonstrated effective antioxidant and enzyme inhibition prospects with effective bioactive molecules, potentially opening the door to a new application in the field of medicine.